Факторна структура біогеометричного профілю постави жінок зрілого віку - Bondar, Olena; Lazko, Olga; Kolos, Mykola; Rychok, Tetiana; Maslova, Olena; Pokropyvnyi, Oleksandr (Fìzične vihovannâ, sport ì kulʹtura zdorov'â u sučasnomu suspìlʹstvì (Online), 2023)
Topicality. As a result of attempts to find out the reasons for the physical health deterioration of mature age women over the past decades, experts have come to the conclusion that a wide range of socio-economic and environmental factors have a negative impact on the health of this category of the population. Another important determinant, in the experts` oppinion, is the adverse, exhausting effect of diets on the female body. However, in the authors` opinion, this situation is primarily due to an unhealthy lifestyle, an inconsistent change of work and rest, and most importantly, a lack of properly selected physical activity. The Research Purpose is to determine the factor structure of the posture biogeometric profile of women aged 36–39 and 40–45. Participants. Tweny-eight 36–39-year-old and respectively twenty-one 40–45-year-old women took part in the study. The research was conducted in compliance with the requirements of the WMA Declaration of Helsinki – Ethical Principles for Medical Research Involving Human Subjects. The Research Methods. Theoretical analysis of special scientific and methodical literature, pedagogical experiment and statistical methods have been used during the study. The Results of the Work. It was established that the first factor involves the indicators of middle adulthood women`s posture biogeometric profile, namely, the chronological stage of 36–39 year-old women, such as: trunk inclination angle (α2), thoracic kyphosis (distance l1), knee joint angle (α3), lumbar lordosis (distance l3), and the second factor reflects: head tilt angle (α1), upper arms symmetry (α5), symmetry of the lower angles of the scapulas (α6). Findings. The change in the factor structure of the biogeometric profile is the result of the reaction and/or compensation of the neuromuscular disorders. Thus, the analysis of human postural deviations should allow for the assessment of musculoskeletal disorders and should be useful for the further corrective and preventive measures procedures. Актуальність теми дослідження. Унаслідок спроб з’ясувати причини погіршення фізичного здоров’я жінок зрілого віку впродовж останніх десятиріч фахівці прийшли до висновку про негативний вплив на здоров’я цієї категорії населення широкого спектра притаманних сьогоденню суспільно-економічних й екологічних чинників. Іще один вагомий детермінант, на переконання фахівців, – це несприятлива, виснажлива дія дієт на жіночий організм. Проте, на нашу думку, таке становище передусім зумовлене веденням нездорового способу життя, непослідовною зміною праці та відпочинку, а основне – нестачею правильно дібраних фізичних навантажень. Мета статті полягає у визначенні факторної структури біогеометричного профілю постави жінок 36–39 й 40–45 років. Учасники. У дослідженні взяли участь жінки 36–39 років n = 28 і 40–45 років n = 21 відповідно. Дослідження проведено з дотриманням вимог Гельсінської декларації Всесвітньої медичної асоціації «Етичні принципи медичних досліджень за участю людини як об’єкта дослідження». Методи дослідження. Теоретичний аналіз спеціальної науково-методичної літератури, педагогічний експеримент, статистичні. Результати роботи. Установлено, що перший фактор охоплює такі показники рівня стану біогеометричного профілю постави жінок другого періоду зрілого віку, зокрема хронологічного етапу 36–39 років, як кут нахилу тулуба (α2), грудний кіфоз (відстань l1), кут у колінному суглобі (α3), поперековий лордоз (відстань l3), а другий фактор відображає кут нахилу голови (α1), симетричність надпліч (α5), симетричність нижніх кутів лопаток (α6). Висновки. Зміна факторної структури біогеометричного профілю є результатом реакції й/або компенсації нервово-м’язової системи, що покладена в основу порушення. Отже, аналіз відхилень у стані постави повинен уможливити проведення оцінки порушення опорно-рухового апарату та має бути корисним для подальшої розробки корекційно-профілактичних заходів.